Examining Energy Consumption Subsides in China: Laying the Groundwork for a Cleaner Environment - Sharp, Robert (Université d'Ottawa | University of Ottawa, 2009)
This paper is based on the idea that the removal of energy subsidies that have associated negative environmental effects could well be the most logical first step for environmental protection. Artificially low government controlled consumer prices in Chin